Vendor Selection and Supply Quotas Determination by Using the Analytic Hierarchy Process and a New Multi-objective Programming Method - Peric, Tunjo; Babic, Zoran; Resic, Emina (Interdisciplinary description of complex systems, 2017)
In this article, we propose a new methodology for solving the vendor selection and the supply quotas determination problem. The proposed methodology combines the Analytic Hierarchy Process (AHP) for determining the coefficients of the objective functions and a new multiple objective programming method based on the cooperative game theory for vendor selection and supply quotas determination. The proposed methodology is tested on the problem of flour purchase by a company that manufactures bakery products. For vendor selection and supply quotas determination we use three complex criteria: (1) purchasing costs, (2) product quality, and (3) vendor reliability.